Supervisi Kepala Madrasah dalam Meningkatkan Kinerja Guru PAI di MAS Al-Mahrusiyah - Mutiar Aslamiyah (Universitas Islam Tribakti Lirboyo Kediri, 2024)
This research is motivated by the necessity to improve the quality of education in order to prepare the young generation who have competitiveness. One way to improve the quality of education is through a supervision program that can improve the performance of a teacher. This study aims to examine how the implementation of supervision in Madrasah Aliyah Private Al Mahrusiyah Lirboyo Kediri. This study uses qualitative research methods with a field research approach, where researchers directly carry out research in the field. The research location is located in Madrasah Aliyah Al Mahrusiyah Lirboyo Kediri. The subjects of this study were the head of the madrasa, waka curriculum and teachers. The object of this research is supervisory competence. Data colleection techniques used three techniques, namely observation, interviews and documentation. The analysis technique uses the Miles and Huberman model, starting from reducing data, presenting data, to drawing conclusions. The results showed that (1) the planning of academic supervision carried out by the head of the madrasah was to formulate the objectives of academic supervision, to arrange an academic supervision schedule by adjusting the school's academic calendar and to develop instruments and determine academic supervision techniques. (2) The implementation of academic supervision activities at Madrasah Aliyah Al Mahrusiyah Lirboyo Kediri there are two stages of supervision carried out, namely academic supervision of learning devices. (3) As for the evaluation and follow-up supervision, namely in the form of indirect coaching and direct coaching, it is rarely carried out.